2020
DOI: 10.15376/biores.15.4.8631-8647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of removal of extractives on the chemical composition and mechanical properties of wood

Abstract: Poplar and pine wood were extracted with water, 1% NaOH (wt%) solution, and benzene:ethanol solution (V1 : V2, 2 : 1) to investigate the governing factors and mechanism by which extractives affect wood structure and mechanical properties. The structure, pore distribution, crystal structure, and mechanical properties of samples were analyzed by Fourier transform infrared spectroscopy (FTIR), adsorption of N2 gas, X-ray diffraction (XRD), and mechanical testing, respectively. The results demonstrated that cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…With an average RAR of 0.46 (0.45 median), the resins are on average 0.6% higher (−1.2% median) and 0.4% lower (+3.4% median) than clear bending MOE and strength, respectively. Studies on other species also found little to no difference between the bending performance of wood with and without extractives [35,[46][47][48] with the exception of Garcia-Iruela, et al [35], who reported a 14% higher bending strength for resinous wood. The bending failure behaviour of timber which is initiated by its low-relative-compression properties [49] indicates that an increase in compression properties would increase bending performance.…”
Section: Effect Of Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…With an average RAR of 0.46 (0.45 median), the resins are on average 0.6% higher (−1.2% median) and 0.4% lower (+3.4% median) than clear bending MOE and strength, respectively. Studies on other species also found little to no difference between the bending performance of wood with and without extractives [35,[46][47][48] with the exception of Garcia-Iruela, et al [35], who reported a 14% higher bending strength for resinous wood. The bending failure behaviour of timber which is initiated by its low-relative-compression properties [49] indicates that an increase in compression properties would increase bending performance.…”
Section: Effect Of Resinmentioning
confidence: 99%
“…With an RAR of 0.58 (0.57 median), resins are on average 0.6% (−2.9% median) higher than the clear samples (Table 2 and Figure 29). Zhao, et al [48] found pine containing extractives was 23% stronger in tension than unextracted pine and they attribute this reduced performance to the reduction in density resulting from the extraction processes. Nevertheless, in their study the extraction processes removed not only extractives but also other components of the cell structure that would affect structural performance.…”
Section: Effect Of Resinmentioning
confidence: 99%